Peningkatan Keterampilan Manajemen Keuangan dan Pemasaran Briket Limbah Kulit Jeruk - Utama, Dana Marsetiya; Rosiani, Tyas Yuli; Baroto, Teguh (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This program aims to enhance the financial management and marketing skills of Karang Taruna Desa Tlogowaru, which has been experiencing difficulties in optimally managing the production of briquettes from citrus waste. This activity is expected to accelerate the development of business scale through more effective cost management and marketing strategies Research methodology: A participatory approach was implemented, involving several stages: initial knowledge assessment, socialization, training, mentoring, and evaluation. Pre- and post-test evaluations were conducted and analyzed using the Wilcoxon test to measure improvements in participants' understanding and skills. Results: The study found significant improvements in participants' abilities to manage cash flow, maintain structured financial records, and design appealing product packaging. Conclusions: This program positively contributes to community empowerment by strengthening local resource-based economic skills and enabling the sustainable development of a citrus waste briquette business. Limitations: This study is limited to a single village and target group, so application in other areas may require contextual adjustments Contribution: This study is beneficial for community empowerment, micro-financial management, and small business marketing and can serve as a reference for similar programs in other communities.